O bairro de Marechal Hermes: da moradia operária à habitação social (1910 - 1956) - Oliveira, Alfredo Cesar Tavares de (2009)
The present thesis aims at investigating the spacial transformations in Marechal Hermes, neighbourhood in the city of Rio de Janeiro, more specifically in the area of the Army which was incorporated by the Union and where the Proletarian Village was built by the Republican President at the time, Marechal Hermes da Fonseca (1910 1914). The core of this research is to relate Marechal Hermes urban morphology with the economic and political changes which distinguish the First Republic (1889 1930) from Vargas Era (1930 1954), taking into account the proletarian housing production. Therefore, among other studies that tackle the development of Rio de Janeiro, studying Marechal Hermes since its project in 1910 until the creation of the social housing or sponsored housing by the Instituto de Aposentadoria dos Servidores do Estado (IPASE), in 1938, turns out to be relevant. In order to explain the urban change in the neighbourhood, this thesis was divided in two moments: the first one deals with the proletarian housing production in Marechal Hermes when the economic liberalism versus President Hermes interventions in that production take place as well as the discussion about the development of Rio de janeiro in 1920; the second one studies Getúlio Vargas government from the Coup d Etat in 1930, when the economic liberalism is substituted for the State intervention of Keynes.This change in the economic politics in Brazil made Vargas choose the urban/industrial model instead of the coffee production economy. In this panorama, the social housing - sponsored by the Institutos de Aposentadorias e Pensões (IAPs), by the government and by workers, whose resources not only targeted at the reproduction of workforce but also at the great distance between workers and left movements, mainly the communist one took place. Even though the sponsored proletarian housing was limited, the IPASE interventions in Marechal Hermes were really successful as they provided the neighbourhood with an enviable urban infra-structure.